Theoretical study of the structural stability of binary semiconductor alloys and cage-like alloy clusters - Fan, Xiaofeng (2009)
In this thesis, the questions about alloy are addressed by the combination of statistical model and first principle calculation. It is mainly focused on the structural stability of the binary semiconductor alloys and cage-like alloy clusters. For the study of semiconductor alloys, a model named quasi-ordered structure (QOS) method is made, by considering the low-temperature nonequilibrium condition of alloy film growth. With the QOS method, the ZnO-based alloy systems including isostructural phase alloys BexZn1−xO and the nonisostructural phase alloys CdxZn1−xO, CdxZn1−xO, MgxZn1−xO and ZnSxO1−x, are investigated systematically. For the study of alloy clusters, a model named color-bond graph (CBG) theory is constructed based on the idea of evaluating the structural stability qualitatively by the bond-counting rule and the effect of local chemical environment for the density of chemical bond. Bonding counting rule is tested to evaluate qualitatively the stability of cage-like cluster (BN)12C12 and used to analyze the structural stability of bulk c-BNC2. With the CBG theory, we study the structural stabilities of cage-like cluster (BN)12C12 and cluster SinC60-n (0<=n<=30).